(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article explores the formation of Uzbek children’s literature and examines the rich legacy left to younger generations by Gafur Ghulam. The distinctiveness of Gafur Ghulam’s literary style lies in his sharp wit and his ability to portray children’s inner world, character, struggles, and joys vividly through humor, often within a single sentence. Moreover, he is highly regarded as a writer who introduced a broad, childlike, and contemplative worldview into literature. His mastery of language is particularly evident in his ability to reveal pressing and sensitive social issues through subtle humor, thereby making them accessible and meaningful to a wider audience.